Study on Nonlinear Dynamics Characteristic of Two-stage Planetary Gear Train - Xiaolu Leng; Xiaosun Wang; Chongshan Lu; Shijing Wu (Jixie chuandong)
The translation and torsion coupled strong nonlinear dynamics model of two-stage planetary gear transmission system is established， and the nonlinear factors such as time-varying meshing stiffness， tooth side clearance and meshing error are introduced， after dimensionless treatment， dynamics equations are established. By using the numerical integration method， system of equations are solved， the nonlinear dynamic response result of the system is obtained， and the bifurcation diagram of the system changing with excitation frequency in the case of different backlash is calculated. Through comprehensive use of phase trajectory， Poincare section and Lyapunov index spectrum， and the system correlation dimension is obtained by the G-P algorithm. The nonlinear dynamics characteristic of two-stage planetary system is studied from the perspective of qualitative and quantitative， the influence of chaotic frequency， into the way of chaos and backlash of two-stage planetary system on the nonlinear characteristics of two-stage planetary gear train is obtained. Some theoretical basis for the study of fault mechanism of two-stage planetary gear system is provided.